PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GIVING QUESTION AND GETTING ANSWER UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 6 BANJARMASIN - KASYPUL ANWAR; GUSTI IRHAMNI (Universitas Mahasaraswati Mataram, 2021)
Improving the quality of education is largely determined by the quality of learning. In this case, the teacher participates in efforts to improve the quality of learning. Teachers should play an active role and position themselves as professional educators. One of the learning methods that can be applied is the GQGA learning method. The GQGA (Giving Question and Getting Answers) method is a method that involves students in repeating the subject matter that has been studied. This research is an experimental study with a randomized pre and post-test control group design. Each group consisting of 10 people, namely the Treatment Group and the Control Group. The results show that (1) the process of implementing the cooperative learning model type Giving Question and Getting Answer to improve the Social Science Learning Outcomes in Junior High School 6 Banjarmasin is carried out by evaluating the learning outcomes for 6 weeks of learning; (2) The application of the cooperative learning model of the Giving Question And Getting Answer type can significantly improve the learning outcomes of Social Sciences in Students of 6 Banjarmasin Junior High Schools.